2020
DOI: 10.1097/scs.0000000000007118
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Fractures Epidemiology and Treatment Plans in the Center of Italy: A Retrospective Study

Abstract: However, its use in an environment without aquatic resistance can cause severe damage. 3 Because of the unusual and unpredictable mechanism of injury, the surgical procedure and specialist teams required to remove a harpoon will depend on the affected structures. 1,2 Harpoon removal from craniofacial structures requires a meticulous approach to avoid damage to noble structures, since it has barb on the spear, with the potential to generate resistance to surgical removal. [1][2][3] If the barb is immobile, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…An European multicenter study reported ORIF as the most common treatment, 24 in the present study, we similarly reported an operative rate of 75.6% and the remaining 24.4% were managed conservatively with serial reviews. Other studies generally reported similar operative rates, Gulateri's Italian study identified young males commonly presented with condylar fractures and had a total operative rate of 66.9% 25 . We adopted ORIF treatment for the symphysis, body, angle, and ramus, whilst the condyle and coronoid process were commonly treated with closed reduction/MMF (Supplementary Digital Content, Table 3, http://links.lww.com/SCS/D387).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…An European multicenter study reported ORIF as the most common treatment, 24 in the present study, we similarly reported an operative rate of 75.6% and the remaining 24.4% were managed conservatively with serial reviews. Other studies generally reported similar operative rates, Gulateri's Italian study identified young males commonly presented with condylar fractures and had a total operative rate of 66.9% 25 . We adopted ORIF treatment for the symphysis, body, angle, and ramus, whilst the condyle and coronoid process were commonly treated with closed reduction/MMF (Supplementary Digital Content, Table 3, http://links.lww.com/SCS/D387).…”
Section: Discussionmentioning
confidence: 90%
“…Other studies generally reported similar operative rates, Gulateri's Italian study identified young males commonly presented with condylar fractures and had a total operative rate of 66.9%. 25 We adopted ORIF treatment for the symphysis, body, angle, and ramus, whilst the condyle and coronoid process were commonly treated with closed reduction/MMF (Supplementary Digital Content, Table 3, http://links.lww.com/SCS/ D387). 26 Complication rates for mandibular fractures can have a variable range with wound infection occurring most frequently.…”
Section: Discussionmentioning
confidence: 99%
“…1 The orbital cavity is one of the most affected anatomical sites, involved in over 40% of all facial injuries, generally followed, depending on the various studies present in the literature, by mandibular trauma. 12 Our retrospective study evaluated the functional esthetic outcome of the subtarsal approach in the treatment of orbital fractures treated in our trauma center from January 2010 to March 2020. The latter has been set to obtain complete documentation and an adequate follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, condylar fractures accounts for around 1820%-of maxillofacial fractures and can be classified based on anatomy into intracapsular condylar head fractures, extracapsular condylar neck fractures and extracapsular subcondylar fracture. [1] Management of condylar fractures can be achieved by either closed or opened reduction according to the amount of displacement. Open reduction and internal fixation (ORIF) is indicated when the amount of displacement is greater than 10o or when the posterior facial height is reduced by more than 2 mm especially with bilateral condylar fractures.…”
Section: Introductionmentioning
confidence: 99%